Impact of Saharan Dust Intrusions on Atmospheric Boundary Layer Height over Madrid - Francisco Molero; Pedro Salvador; Manuel Pujadas (Atmosphere)
Atmospheric pollution caused by aerosols deteriorates air quality, increasing public health risks. Anthropogenic aerosols are usually located within the atmospheric boundary layer (ABL), which presents a daytime evolution that determines the air pollutants’ vertical mixing of those produced near the surface and, therefore, their ground-level concentration from local sources. Precise and complete characterization of the mixing layer is of crucial importance for numerical weather forecasting and climate models, but traditional methods such as radiosounding present some spatial and temporal limitations. Better resolutions have been obtained using lidar, which provides the aerosol vertical distribution. A particular type of lidar, the ceilometer, has demonstrated continuous measurement capabilities, providing vertical profiles with sub-minute time resolution and several-meter spatial resolution. Advanced methods, such as the recently developed STRATfinder algorithm, are required to estimate the ABL height in the presence of residual layers. More complex situations occur due to the advection of aerosols (e.g., due to long-range transport of desert dust, volcanic eruptions, or pyrocloud convection), producing a lofted layer in the free troposphere that may remain decoupled from the local ABL but can also be mixed. Aerosol-based methods for determination of the ABL height are challenging in those situations. The main objective of this research is the assessment of the impact of Saharan dust intrusions on the ABL using ceilometer signals, over a period of four years, 2020–2023. The ABL height database, obtained from ceilometer measurements every hour, is analyzed based on the most frequent synoptic patterns. A reduction in the ABL height was obtained from high dust load days (1576 ± 876 m) with respect to low dust load days (1857 ± 914 m), although it was still higher than clean days (1423 ± 772 m). This behavior is further studied discriminating by season and synoptic patterns. These results are relevant for health advice during Saharan dust intrusion days.